The Role of the Family in Building Children's Morale - Mely Putri Almanda; Abdurrahman Abdurrahman (Program Studi Bimbingan dan Konseling, Fakultas Ilmu Pendidikan, Universitas Negeri Medan, 2021)
The motivation of this paper is to describe the role of the family in building morals through an exploration type by looking at what methods families use in educating children to build children's morals through family counseling analysis. Furthermore, the role of the family in building the morale of children is analyzed through family counseling as a guide to the importance of building harmony with individuals in the family, especially with children. This research is considered important because lately the lack of morality in children is caused by various factors that occur at this time. It is not only caused by the education of parents, but also due to environmental influences and the continuous development of the times. This research uses the library research method with a theoretical approach. The results of this description are obtained from various existing studies, and literature. The scope of methods that have been used by families in building children's morality is more striking, namely the Islamic religious education method, the method of communication, and the method of moral education.